Diversity of benthic diatoms and correlation with water quality of Yom River, Thailand - Ekkacahi Yana (2018)
Yom River is the main river of Northern Thailand, it is the main tributary of Nan River and run to Chao Phaya River which is the main river in the middle part of Thailand. In this study, 10 sampling sites along Yom River were selected. The main physical and chemical parameters were measured and human activities along this river were also recorded during June 2011- May 2012. Cluster analysis indicated the effect of human activity, seasonal change and geological characteristic in each area.The upper part is located at limestone mountainous area and some forest destruction in the upper part which cause high alkalinity, electro-conductivity and high leaching in rainy season. The middle part was mainly affected by forest destruction for agriculture and household activity which dispose contaminant of nutrient and organic matter into water body directly. The lower part was mainly affected by household waste which leads to nutrient contaminant in this area. Base on AARL-PC Score, the water quality in the upper most part was clean to moderate and moderate in the middle and lower parts. For benthic diatoms, 199 species were found and classified to GeneraAchnanthidium, Cocconeis, Cymbella, Mayamaea, Melosira, Navicula, Nitzschia, Planothidiun, Rhopalodia, Seminarvis and Ulnaria. High relative abundance ( > 1%) of them were used to find the trend to using as bioindicator with water properties. In canonicalcorrespondence analysis, Naviculacryptotenella, Naviculasinulata, NaviculagermainiiUlnaria ulna, Gomphonemalagenulum, Nitzschiagracilliformis, Nitzschiapalea, Nitzschiapumila and Mayameaagrestishad a trend to indicate the water which displayed high turbidity, water temperature and contamination of nutrients and BOD. Moreover, Achananthidiumminutissimum, Achnanthidiumstraubianum,Cocconeisplacentula, Cymbellaturgidula, Gomphonemajavanicum, Naviculamicrodigitoradiata, Planothidiumfrequentissimum,Rhopalodiamusculu,sGyrosigmascalproides. Melosiravarians andSeminavisstrigosa could be used to high DO, elctroconductivity, alkalinity and pH. © Research India Publications.